Stimulasi Komunikasi Lisan melalui Kegiatan Menggambar dan Becerita di KBTK Al Hikmah Surabaya - Zumara, Noor Iz; Kristanto, Andi; Adhe, Kartika Rinakit; Fitri, Ruqoyya (Pendidikan Guru PAUD Universitas Persatuan Guru Republik Indonesia Semarang, 2025)
This study was motivated by the post-COVID-19 pandemic phenomenon, which revealed that early childhood children experienced challenges and delays in developing communication skills. Communication skills need to be fostered from an early age. This study aims to describe the use of drawing and storytelling activities as a strategy to stimulate oral communication skills among 5–6-year-old children in Group B of TK Al Hikmah Surabaya. Using a descriptive qualitative approach, the research involved 20 children as subjects over a period of two months. Data were collected through observation, interviews, and documentation. Observations were conducted during the drawing and storytelling activities, focusing on visible behaviors and the storytelling processes carried out by the children. Interviews were conducted with teachers and parents to explore perceived developments in the children's communication skills. The results showed that free drawing and storytelling activities increased the frequency of children's speech, enriched their vocabulary, improved sentence structure, and fostered their confidence in expressing ideas orally. The study concludes that this visual-verbal strategy is highly effective in supporting early childhood communication development and is suitable for integration into character-based Islamic education. Drawing and storytelling activities are strongly recommended as a regular approach in early childhood education. This approach should be integrated into curricula that emphasize character formation and holistic language development.